Strategies for the Analysis of Oncogene Overexpression: Studies of the neu Oncogene in Breast Carcinoma. Issue 2 (28th January 2016) - Naber, Stephen P.; Tsutsumi, Yutaka; Yin, Samuel; Zolnay, Stephen A.; Mobtaker, Hamid; Marks, Paula J.; Mckenzie, Sara J.; Delellis, Ronald A.; Wolfe, Hubert J.
Abstract : The development of a consistent strategy for the analysis of oncogene expression at the cellular level is essential for understanding the roles of these genes in the development and progression of human neoplasia. Detection of the neu oncogene products in breast carcinoma was selected as a model for analysis of oncogene expression. Fifty-two primary human breast carcinomas were evaluated by quantitation of neu DNA amplification and mRNA expression and by localization of neu mRNA and protein (pi 85) at the cellular level by in situ hybridization (ISH) and immunohistochemistry (IHC). The specificity and sensitivity of the molecular and immunologic probes for neu were established with the use of genetically engineered cell lines that overexpressed either neu or epidermal growth factor receptor (EGFR). Twenty-nine percent of breast carcinomas demonstrated neu DNA amplification and mRNA overexpression, and there was close correlation between the level of neu mRNA expression and detection of neu gene products by ISH and IHC. Thirty-two percent of carcinomas demonstrated neu mRNA overexpression by ISH. The immunohistochemical method using TA1 monoclonal antibody for pi 85 was exquisitely sensitive in acetonefixed frozen sections and provided an excellent approach for judging overexpression as confirmed by the various molecular analyses. All areas of nonmalignant breast epithelium stained weakly, and a wide range of staining intensity was observed in malignant breast epithelium, with 31 % of carcinomas judged to be pi 85 overexpressors. Heterogeneous expression of pi 85 was seen in some carcinomas. This study provides a strategic approach for the evaluation of oncogene expression in human tumors.